An Exploratory Study of Ethical Perspectives of Celebrity Endorsements - Joel Gnanapragash, T.; Sekar, P. C. (Indian Journal of Marketing, 2013)
Ethics in business is a much discussed phenomena now, especially after the news about the increasing number of corporate executives indulging in scams. However, it is essential to comprehend the relevance of ethics in each domain of management. The interesting development in the field of marketing communications necessitates an inquiry into how consumers generally feel about ethics in marketing communication. An increasingly notable trend in the advertising industry is "Celebrity Endorsements". Against the background of celebrity endorsement theories and celebrity endorsement strategies, the research paper presents a new term "celebrity ethics" from the consumers’ point of view. Essentially, it delineates the "consumer perceived celebrity ethics" as an important dimension of celebrity endorsements. More particularly, it lists celebrities who are perceived as highly ethical. Thus, we believe that the results may provide valuable inputs to advertisers as well as to socially responsible organizations that are seeking to rope in celebrities who would be ethically fitting to act as endorsers for their products or services.